ANALYSIS OF COVID-19 VACCINATION COVERAGE AND ADHERENCE AMONG THE ELDERLY POPULATION OF ANÁPOLIS, GOIÁS (CIPEEX, 2025)
Vaccination is an effective and highly cost-beneficial public health policy for preventing and controlling infectious diseases. In Brazil, vaccination coverage has been increasing, despite the challenges faced by an emerging country. However, factors such as poor adherence to vaccination campaigns can limit program effectiveness. Identifying barriers and challenges that impede optimal vaccination adherence is therefore essential.This study aimed to analyze COVID-19 vaccination coverage and adherence among the elderly population in Anápolis, Goiás. A cross-sectional, descriptive, and quantitative study was conducted using a semi-structured questionnaire that assessed vaccination coverage, adherence, and knowledge regarding the COVID-19 vaccine. A total of 35 elderly individuals were surveyed, most of whom were women (68.6%) aged between 60 and 65 years. Regarding the COVID-19 vaccine, 74.3% knew its purpose, but most were unaware of how it works in the body. Adherence to the first and second doses was high (77.1% and 68.6%, respectively), but only 17.6% completed the vaccination schedule with booster doses.The study concludes that there was high initial adherence to COVID-19 vaccination among elderly residents of Anápolis-GO, with confidence in the vaccine’s efficacy and safety. However, adherence to booster doses was low, highlighting challenges such as fear of adverse effects and lack of medical recommendation.
Keywords: COVID-19 infections; Vaccination coverage; Knowledge